81 Injuries caused by law enforcement among young people: disparities and trends among California emergency department and hospital patients, 2005–2014. (5th May 2020) - Farkas, Kriszta; Duarte, Catherine; Ahern, Jennifer
Abstract : Police violence is an important public health issue. Although research on police violence has substantially grown, few studies have examined its burden among young people. Given a broader literature that documents lasting adverse effects of early-life exposure to trauma and disproportionate policing of Black youth linked to racialized constructions of their being older and dangerous, further inquiry is warranted. This study examined the demographic and temporal distributions of injuries caused by law enforcement, severe enough to require clinical care, among young people. Using statewide data on all hospitalizations and emergency department visits in California, 2005–2014, we identified patients, ages 19 years or younger, with ICD-9-CM external cause of injury codes for legal intervention (LI) injury, and calculated rates using Census population estimates. From 2005–2014, 13, 855 young people in California were treated for LI injury. Non-Hispanic Black males, ages 15–19 years, had the highest rate overall (217.5 per 100, 000 person-years [PYs]), over three times that among same aged non-Hispanic White males (64.1 per 100, 000 PYs). Among 10–14-year-olds, Black boys had five times (22.2 per 100, 000 PYs) the LI injury rate as White boys (4.3 per 100, 000 PYs), and, notably, the rate among Black girls (8.9 per 100, 000 PYs) was twice and six times the rates, respectively, among White boys and White girls (1.5 per 100, 000 PYs). Trends in annual rates also varied by race. Rates among White youth increased by 29.3%, peaking in 2009, but returned below the 2005 rate by 2014, whereas rates among Black youth increased by 63.6% by 2009, but did not return to the 2005 level by 2014. Results indicate that the burden of LI injuries among young people substantially varies by minoritized identity; in particular, Black boys and girls experience dramatically greater rates of LI injury, and inequities are even greater at younger ages.